EXPERIMENTAL STUDY CONCERNING MASS TRANSFER INSIDE THE PACKED COLUMN OF SOLAR COOLING LIQUID DESICCANT SYSTEM USING COUNTER FLOW CONFIGURATION - Rahmanto, R Hengki (JURNAL ILMIAH TEKNIK MESIN, 2015)
Sistem desiccant telah diusulkan sebagai alternatif untuk menghemat energy dibandingkan pendinginudara kompresi uap untuk menangani beban laten. Penggunaan desiccant cair menawarkan beberapakeuntungan desain dan performa dibandingkan desiccant padat, terutama ketika energi matahari digunakanuntuk proses regenerasi. Desiccant cair mengalami kontak dengan gas di dalam packed column dan perpindahanpanas dan perpindahan massa akan terjadi. Paper ini untuk mempelajari perpindahan massa dan perpindahanpanas di dalam packed column pada dehumidifier dan sistem regenerator. Dan nantinya, laju dehumidifikasi danregenerasi yang dipengaruhi oleh laju aliran desiccant, temperatur dan kelembaban udara, dan temperaturdesiccant dan semua variasi tersebut akan mempengaruhi performa dari sistem tersebutÂ Desiccant systems have been proposed as energy saving alternatives to vapor compression airconditioning for handling the latent load. Use of liquid desiccants offers several design and performanceadvantages over solid desiccants, especially when solar energy is used for regeneration. The liquid desiccantscontact the gas inside the packed column and the heat transfer and mass transfer will occur. This proposal istrying to study the mass transfer and heat transfer inside the packed column of dehumidifier and regeneratorsystems. And later on, the rates of dehumidification and regeneration that were affected by desiccant flow rates,air temperature and humidity, and desiccant temperature and all that variation will influence the performance ofthe systems.Key words: solar cooling, dehumidification, regeneration, lithium chloride